A multi-physics transient wear model for helical gear pairs. (May 2022) - Walker, J.; Mohammadpour, M.; Theodossiades, S.; Bewsher, S.R.; Offner, G.; Bansal, H.; Leighton, M.; Braunstingl, M.; Flesch, H.-G.
Abstract: This study combines the use of a Tooth Contact Analysis (TCA) model for helical gear pair conjunctions with a multifaceted tribological model, implicitly coupled with a multi-body dynamic system. A reduced order 2-D Elastohydrodynamic Lubricant (EHL) film thickness prediction facilitates the estimation of viscous and boundary friction with a Greenwood-Tripp asperity model, as well as a lubricated wear methodology. An implicit approach is used to capture progressing wear upon gear teeth with consideration of gear microgeometry. The use of the numerical EHL model gives new insights to the coupled evolution of wear and dynamics on efficiency and NVH throughout the component's life cycle. Highlights: Tribo-dynamic simulation of an electric transmission helical gear pair. Coupled interaction of gear pair wear and dynamic loading produces evolving tooth wear patterns. Reduced order 2-D elastohydrodynamic lubrication modelling enables efficient computation of film thickness. Boundary and viscous friction are evaluated throughout meshing cycles with respects to evolving wear patterns.